Corneal Evaluation in Patients With Parkinsonism on Long-Term Amantadine Therapy. Issue 9 (September 2019) - Daggumilli, Satyasudha; Vanathi, Murugesan; Ganger, Anita; Goyal, Vinay; Tandon, Radhika
Abstract : Purpose: To evaluate the progression of corneal endothelial changes in patients with Parkinson disease (PD) on long-term oral amantadine therapy. Methods: A prospective comparative longitudinal observational study of 90 patients (180 eyes) with PD on more than 6 months of oral amantadine therapy, 30 amantadine naive patients with PD, and 30 healthy controls (age and gender matched). Corneal endothelial cell parameters (endothelial cell density, percentage hexagonality of the cells, and coefficient of variation) and corneal subbasal nerve fiber layer changes were studied over a follow-up period of 1 year. Results: The amantadine patients with PD group had a statistically significant decrease in endothelial cell density (1.51% vs. 0.94% vs. 0.55%) ( P = 0.04), decrease of percentage hexagonality of the cells (4.98% vs. 3.56% vs. 2.31%) ( P = 0.01), and increase of coefficient of variation (6.12% vs. 4.80% vs. 3.30%) ( P = 0.03) compared with amantadine naive patients with PD and controls, respectively. Analysis of changes in the patients with PD based on the daily dosage of amantadine showed greater change in endothelial parameters in patients who were on 400 mg amantadine. Conclusions: Long-term amantadine therapy seems to effect changes on corneal endothelium.